PENGARUH PENGGUNAAN TEKNIK COPY THE MASTER TERHADAP KETERAMPILAN MENULIS TEKS FABEL SISWA KELAS VII SMP NEGERI 1 PARIAMAN - Sari, Novita; Gani, Erizal; Zulfikarni, Zulfikarni (Universitas Negeri Padang, 2018)
ABSTRACTÂ This article was written to illustrate the effect of using technic copy the master to writing skill of fable text of VII students of SMP Negeri 1 Pariaman. This research data is a score in the skills of writing fable texts before and after using technic copy the master (next on abbreviated CTM) .This study has three results. First, the skills of writing fable texts before using technic CTM in the qualification Enough (C). Second, the skill of writing the text of the fable of the students of grade VII SMP Negeri 1 Pariaman after using the technic CTM is qualified More than Enough (Ldc). Third, based on the t test concluded that there is a significant influence on the skill of writing fable text because thitung> ttabel (5,67> 1,70).Â Kata kunci: pengaruh, teknik copy the master, teks fabel